Solicitors and the wider community, 1975-1976 - Podmore, David (UK Data Service, 1981)
Research carried out in the United States indicates that lawyers have a high level of participation in activities in the wider community. This survey gathered information on the participation in extra-professional activities of West Midlands solicitors.